Rooted in and Routed through Christ: Friendship in An Anglican-Methodist Covenant - Gee, Ruth M. (Ecclesiology, 2025)
Written in the third decade of An Anglican-Methodist Covenant, this essay proposes the concept of friendship as a lens through which to view the covenant relationship and as the basis of apologetic for the covenant and wider ecumenism. A distinctive Christian understanding of friendship as rooted in and routed through Christ is proposed on the basis of Scripture and theology with particular reference to John 15:12–17. It is argued that a focus on friendship understood in this way resonates with Methodist ecclesiology and with experience, while being of contemporary relevance. Furthermore, the distinctiveness of friendship rooted in and routed through Christ allows us to continue to grow in covenant when we differ in deeply held responses to specific issues.